Pengaruh Kampanye Public Relations Digital terhadap Interaksi Audiens pada Konten Kolaborasi Instagram - Sulu, Nopri Ramadan (Communicology: Jurnal Ilmu Komunikasi, 2025)
The development of social media has significantly transformed Public Relations practices from one-way communication into audience centered engagement. Instagram, as a highly visual and interactive platform, is widely utilized by organizations to implement digital Public Relations campaigns through collaborative strategies. This study aims to examine the influence of the #PastiAdaJalan Public Relations campaign, a collaboration between Gojek and Band Perunggu, on audience interaction on Instagram. This research employs a quantitative approach using a survey method. Data were collected through an online questionnaire distributed to 100 respondents who follow the @gojekindonesia Instagram account and have viewed the #PastiAdaJalan campaign content. Data analysis was conducted using simple linear regression with the assistance of IBM SPSS software. The results indicate that the #PastiAdaJalan campaign has a significant effect on audience interaction. The regression equation Y = 6.054 + 0.318X demonstrates a positive relationship between the Public Relations campaign and audience interaction. Furthermore, the coefficient of determination (R²) value of 0.606 indicates that 60.6% of the variation in audience interaction can be explained by the campaign. These findings suggest that collaborative Public Relations campaigns on social media are effective in building attention and positive brand perception, although they do not fully encourage active audience participation. This study is expected to contribute to the development of digital Public Relations campaign strategies on social media platforms.